2020
DOI: 10.4314/as.v19i1.3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of malting periods on the nutrient composition, antinutrient content and pasting properties of mungbean flour

Abstract: Mungbean grain has great potentials for product development, being rich in protein and other nutrients. This study evaluated the effects of malting periods on the nutrient composition, antinutrient content and pasting properties of malted mungbean flour. Flour samples were produced form mungbean grain malted for 24, 48, 72 and 96 h and assayed for proximate composition, selected mineral contents, vitamins A and B1, antinutrient contents, functional and pasting properties. Results showed that increasing the mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…The result is similar to the studies on germinated legumes, mung beans, goat pea, and light brown speckled kidney beans [33,37]. Several studies have shown that sprouting increases the protein content of lupin, peas, chickpea, moth beans, soya beans, and mung beans [32,34,35,40,94,[154][155][156]. Researchers have also observed lower protein content in sprouted legumes, resulting from seed types and conditions of sprouting [34,35,157,158].…”
Section: Effect Of Steeping and Sprouting Time On The Protein Content...supporting
confidence: 80%
See 1 more Smart Citation
“…The result is similar to the studies on germinated legumes, mung beans, goat pea, and light brown speckled kidney beans [33,37]. Several studies have shown that sprouting increases the protein content of lupin, peas, chickpea, moth beans, soya beans, and mung beans [32,34,35,40,94,[154][155][156]. Researchers have also observed lower protein content in sprouted legumes, resulting from seed types and conditions of sprouting [34,35,157,158].…”
Section: Effect Of Steeping and Sprouting Time On The Protein Content...supporting
confidence: 80%
“…The hilum is a scar on the legume seeds that marks the attachment point to the seed, where water enters the seed coat and cotyledon [92]. Once the seed coat is fully hydrated, it allows for water uptake by diffusion until the equilibrium moisture content is achieved [91,93,94].…”
Section: Water Absorption Of Steeped Bambara Groundnut Seedsmentioning
confidence: 99%
“…Seeds of greengram contain an abundance of major food nutrients including protein, about 30% of dry matter (DM) (AVRDC, 2012), carbohydrate up to 45% of DM, fiber about 6.5% of DM (Heuzé et al, 2015), and some essential amino acids which explains its revered position as the most nutritious pulse known (Anjum et al, 2011). In addition, the protein, ash, fiber and mineral contents of mungbean can significantly be improved by increasing the malting periods (Onwurafor et al, 2020). Medicinally, mungbean has been used in China and India in the prevention and treatment of varied health-related ailments due to the overwhelming high levels of phytochemicals including vitexin, isovitexin, total phenols, flavonoids and other compounds in the grains and sprouts (Cao et al, 2011;Kim et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…During germination, the endogenous enzymes of the legumes were activated. Kayembe and Rensburg, (2013) [15] and Onwurafor et al, (2020) [17] reported the decreased fat content in germinated grains. The carbohydrate content of experimental and control samples (C2) showed significant decrease (p<0.05) after malting than that of raw samples.…”
Section: Proximate Compositionmentioning
confidence: 95%